2003
DOI: 10.1177/154405910308201115
|View full text |Cite
|
Sign up to set email alerts
|

Survivin, a Potential Early Predictor of Tumor Progression in the Oral Mucosa

Abstract: Survivin is a recently described apoptosis inhibitor selectively over-expressed in most tumors. Immunohistochemistry was used to investigate a potential role of survivin as an early predictor of malignant transformation in precancerous and cancerous lesions of the oral cavity. Survivin was present in 10/30 cases (33%) of oral precancerous lesions without malignant progression, and in 15/16 cases (94%) of oral precancerous lesions evolved into full-blown squamous cell carcinoma. Tumors that progressed from thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 27 publications
4
81
2
1
Order By: Relevance
“…HPV-positive OSCC lesions with higher levels of survivin expression could have a worse clinical outcome: survivin could stop apoptosis and promote cell transformation. 64 Thirdly, all HPV-negative cases were smokers (100%), while only 44% of HPV-positive cases were smokers. Tobacco smoking appears to protect subjects from HPV infection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…HPV-positive OSCC lesions with higher levels of survivin expression could have a worse clinical outcome: survivin could stop apoptosis and promote cell transformation. 64 Thirdly, all HPV-negative cases were smokers (100%), while only 44% of HPV-positive cases were smokers. Tobacco smoking appears to protect subjects from HPV infection.…”
Section: Discussionmentioning
confidence: 95%
“…This is in agreement with previously reported links between high levels of survivin expression and worse prognosis of the neoplastic lesions along with better prognosis in HPV-positive OSCC. 57 In retrospective trials, survivin expression has been correlated with reduced overall survival in several solid tumors, [58][59][60][61][62][63] especially in OSCC; 27,64,65 similarly, HPV infection could influence oral carcinogenesis, consistently with results suggesting that HPV-positive patients have significantly reduced overall and disease-specific mortality. 22,66 Besides Gillison et al, 57 Herrero et al 34 suggested HPV-positive OSCC as a distinct small subgroup of tumors with different biomolecular and clinical behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Cells proliferating at a physiologic rate express this receptor in both the membrane and the cytoplasm. When EGFR is located only in the membrane, the speed of cell response to proliferative stimuli may be increased; on the other hand, when EGFR is found only in the cytoplasm (i.e., internalized or inactive), a slower response may be observed [24][25][26]. In the sample assessed in our study, EGFR immunolabeling was observed mainly in the cytoplasm in basal and suprabasal layers of KOTs, and in the suprabasal layer of DCs.…”
Section: Discussionmentioning
confidence: 97%
“…In an attempt to better understand the mechanisms regulating odontogenic epithelium, this study was designed using DCs as representatives of odontogenic epithelium in cysts, KOTs as representatives of odontogenic epithelium in tumors, and PFs as the physiological pattern of odontogenic epithelium. Moreover, based on previous reports, three proteins were selected for the assessment of different aspects as follows: Ki-67, related to cell proliferation [8,[20][21][22][23]; EGFR, related to the capacity of cells to respond to stimuli [13,24,25]; and survivin, related to inhibition of apoptosis [26][27][28][29]. The aim of this study was to evaluate the biological profile of odontogenic epithelium by immunolabeling of EGFR, Ki-67 and survivin in a neoplasm (KOTs), a cystic lesion (DCs), and in PFs.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of variance was performed and the differences between means were determined using the Student's t-test * Significantly greater than control (fibroma) (P \ 0.05) lesion [7,8,11]. Past studies have investigated convincingly, loss of heterozygosity, use of fluorescence and molecular markers such as telomerase, [12] epidermal growth factor receptor [13], survivin [14], hypermethylation of the promoters of specific genes [15], and p53 expression [16] to assess the probability of conversion of oral lesions to cancer. Over the years, analysis of DNA content (DNA ploidy) has been suggested to be an important predictor of malignant potential of leukoplakia or erythroplakia [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%